The reappearance of long-finned gurnard Chelidonichthys obscurus (Scorpaeniformes: Triglidae) in the western English Channel. (7th May 2014) - Burt, Gary J.; Ellis, Jim R.
Abstract : Records of long-finned gurnard Chelidonichthys obscurus in the western English Channel are rare. Prior to this study, reported incidences were largely restricted to the 19th Century and it appears to have been unrecorded in this well-studied ecosystem over much of the 20th Century. Data from a contemporary trawl survey in and around Lyme Bay (1989–2013) indicate that this species ( N  = 58) was only present during the period 2005–2013. These data and records from other surveys ( N  = 24) indicate a localized population may persist in an area just south of Start Point (64–77 m water depth), although it can occasionally occur in shallower inshore waters. A sub-sample of fish was collected to provide additional information on their morphometrics, meristics and diet. Meristic counts were generally in accord with earlier studies as were observations on their diet, which showed that they fed almost exclusively on crustaceans, especially mysids.